1988
DOI: 10.1007/bf02470839
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the disappearance rate of indocyanine grenn

Abstract: Time-associated changes in the disappearance rate of indocyanine green from the blood (K.ICG) as an index of liver function, were studied. Blood was drawn 5 times at 3-minute intervals from 32 patients. Early, intermediate, and late K.ICG values were 0.087 +/- 0.040, 0.082 +/- 0.038, and 0.076 +/- 0.033 min-1, respectively, showing serial decreases. When blood was drawn 8 times at 2-minute intervals from 22 other patients, the means of the K.ICG values at 11 time points showed a nearly linear relationship (r =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Previous basic and clinical reports have suggested that dynamic quantitative liver function tests provide more accurate assessment of the specific aspects of liver function than passive assessments [ 23 25 ]. Some researchers have classified ICGR15 as a dynamic liver function test, but ICGR15 does not strictly reflect time-associated changes in the concentration of ICG, because evaluation is only made from two time points, before and 15 min after injection [ 18 , 23 25 ]. Yokoyama et al reported preoperative liver functional assessment using ICG-K as a more useful parameter for predicting PHLF than ICGR15 [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous basic and clinical reports have suggested that dynamic quantitative liver function tests provide more accurate assessment of the specific aspects of liver function than passive assessments [ 23 25 ]. Some researchers have classified ICGR15 as a dynamic liver function test, but ICGR15 does not strictly reflect time-associated changes in the concentration of ICG, because evaluation is only made from two time points, before and 15 min after injection [ 18 , 23 25 ]. Yokoyama et al reported preoperative liver functional assessment using ICG-K as a more useful parameter for predicting PHLF than ICGR15 [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative assessment of liver function by ICGR15 similarly involves timing bias in blood sampling and should be evaluated accurately at 15 min after ICG injection. Conversely, ICG-K, which is calculated by multiple blood samplings after injection, reflects changes in ICG concentration over time and is known to provide functional assessment of the liver with minimal timing bias for blood sampling [ 18 ]. Kumasawa et al reported that ICG-K calculated using blood samples at 3-min intervals after injection correlated closely with results calculated from values at 2-min intervals [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations